Microbiological Biosafety, Multiple Drug Resistance and Functional Diversity of Bacteria Associated with the Surfaces of Raw Vegetables - Farooq NISMA; Raheem ASIF; Ali BASHARAT (Tehran University of Medical Sciences, 2017)
Microbiological Biosafety, Multiple Drug Resistance and  Functional Diversity of Bacteria Associated with the Surfaces of Raw Vegetables